Comparison of methods for cultivation and isolation of Chlamydia trachomatis. - Benes, S (1982)
McCoy cells treated with cycloheximide, iododeoxyuridine, and DEAE-dextran and untreated McCoy cells were inoculated with two stock strains of Chlamydia trachomatis and with 231 urethral specimens from men, 53 (23%) of which contained C. trachomatis. Isolation rates, number and quality of inclusions, and quality of the cell monolayers were compared. There were no significant differences between the isolation rates in the four systems, although the most isolations were made in the untreated and cycloheximide-treated cells. Cycloheximide-treated cells produced, from both the clinical specimens and the two stock strains, significantly more inclusions than any of the other systems. The monolayer of the cycloheximide-treated cells and the inclusions that grew in these cells were optimal for examination and detection of C. trachomatis.